Factors Affecting the Quality of Palembang Regional Government Financial Reports in South Sumatra, Indonesia - Setyadi, Bakti; Helmi, Sulaiman; Azizah, Isna Khorul; Sartika, Dewi (Ilomata International Journal of Management, 2024)
This research aims to identify the factors influencing the quality of the Palembang regional government's financial reports. The factors examined include the application of Government Accounting Standards, the Internal Control System, Human Resources Competency, and the Role of Internal Audit. The study employs a qualitative research method with data collected through interviews. The findings reveal that the application of Government Accounting Standards, the Internal Control System, Human Resources Competency, and the Role of Internal Audit significantly affect the quality of the financial reports. The implications of this research suggest that local governments should enhance the implementation of Government Accounting Standards, strengthen the Internal Control System, improve Human Resources Competency, and optimize the role of internal audit to elevate the quality of financial reports.